The linking of service quality, trust, and innovation toward taxpayer’s satisfaction - Mohamad Firdaus, Abdul Rahim (2023)
The provision of quality government services is becoming increasingly important, and the public sector is striving to match private companies when delivering exceptional services. The Inland Revenue Board of Malaysia (IRBM) is central in providing direct services to clients on tax matters. However, concerns have been raised about the quality of services the IRBM provides. This study examines the relationships between service quality, customer trust, and taxpayer satisfaction with IRBM and the mediating influence of innovation on these linkages. A quantitative research design was employed in this study. A total of 384 questionnaires were distributed to Malaysian taxpayers in eight IRBM Northern Region branches. The data were analyzed using partial least squares – structural equation modeling (PLS-SEM) via SmartPLS 3. The results reveal a significant relationship between service quality, customer trust, and taxpayer satisfaction with IRBM. Higher service quality directly increases satisfaction, while higher customer trust leads to higher taxpayer satisfaction with IRBM services. Moreover, innovation acts as a mediator and influences the impact of service quality and customer trust on taxpayer satisfaction with IRBM services. Fostering innovation in service delivery enhances service quality, builds customer trust, and boosts customer satisfaction with IRBM. As for practical implications, stakeholders should make informed decisions and implement effective strategies to improve service quality, foster customer trust, and ultimately enhance taxpayers’ satisfaction with IRBM. In terms of theoretical implications, the present research applies the Expectation Disconfirmation Theory in the proposed framework and discovered significant relationships between service quality, customer trust, and taxpayer satisfaction with IRBM. Another important discovery concerns the mediation of innovations in these relationships.